Representations of Social Cognition of TV One and Kompas TV Journalists in the Construction of News Discourse on Corruption: Critical Discourse Analysis - Rivaldi, Sacandra Aji; Mardikantoro, Hari Bakti (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Criminal acts of corruption causing the destruction of human prosperity could be news discourse that receives lots of public’s serious attention. The difference of perspectives on corruption cases has impacted on the production of news discourse because of the influence of mass media’s backgrounds, knowledge, and ideologies. This present study aims to describe and analyze practices of the production of news discourse on corruption portrayed in TV One and Kompas TV mass media based on the van Dijk’s model of critical discourse analysis. The data presented in this qualitative study were collected through observation and interview. The findings reveal that TV One used person, self-presentation, role, and event schemes in the construction of news discourse on corruption. The use of these schemes was based on the priority of news values. Meanwhile, Kompas TV employed the same schemes as TV One did. The use of the schemes was deemed in terms of the ideology referred by this mass media, namely: “fortiter in re, suaviter in modo” (“firmly in action, gently in manner”). This ideology was used in the production of the news discourse so that the classical proverb in journalism “menghibur yang papa, mengingatkan yang mapan” (“comfort the afflicted, afflict the comfortable”) affirmed in this mass media. Both of Indonesia’s television channels tended to concern the control of cognition in producing the news discourse on a graft case.